Negative Affect, Fatalism, and Perceived Institutional Betrayal in Times of the Coronavirus Pandemic: A Cross-Cultural Investigation of Control Beliefs - Bachem, Rahel; Tsur, Noga; Levin, Yafit; Abu-Raiya, Hisham; Maercker, Andreas (Frontiers in Psychiatry, 2020)
Background. A growing number of studies report that the COVID-19 pandemic has resulted in a large number of aversive psychological reactions and created a global mental health crisis. However, the specific mechanisms underlying the negative emotional reactions as well as the differences between countries are only beginning to be explored. The present study examined the association of COVID-19-related fear and negative affect in Israel and Switzerland. The mediating roles of three control beliefs were explored, namely, fatalism, locus of control, and perceived institutional betrayal. Method. General population samples of 595 Swiss and 639 Israeli participants were recruited and completed an online self-report survey. Moderated Mediation using multigroup path analysis models for the two samples were conducted and compared using AMOS. Results. The multigroup path model had excellent fit for both samples. The different paths were moderated by country affiliation. Higher levels of COVID-19-related fear were associated with negative affect to an equal extent in both samples. COVID-19-related fear was associated with higher reports of institutional betrayal and a lower locus of control in both samples. Higher COVID-19-related fear was associated with lower fatalism in the Swiss sample only. In both samples, institutional betrayal mediated the association between COVID-19-related fear and negative affect, however, locus of control was a mediator in the Israeli sample only. Conclusion. The current results suggest that the reaction of the government was of crucial importance with regard to the emotional state of the two populations. Interestingly, while in the context of adversity fatalism is generally considered a risk factor for mental health, during the time of the pandemic it seems to have had protective qualities among the Swiss population. Interventions that strengthen the personal locus of control have the potential to mitigate the negative affect in Israel but not in Switzerland. Despite the fact that COVID-19 is a global phenomenon, prevention and intervention strategies should be adjusted to local contexts.